2010
DOI: 10.1002/ardp.200900217
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conjugates of Aspirin with Phenolic Acid as Anti‐inflammatory Agents Having Significantly Reduced Gastrointestinal Toxicity

Abstract: A series of novel conjugates of aspirin with natural phenolic acid antioxidants connected through a diol linker were designed and synthesized as potential bifunctional agents combining antioxidant and anti-inflammatory activity for reducing gastrointestinal toxicity. In general, the conjugates were found to be efficient antioxidants and many of them demonstrated much more potent anti-inflammatory activity than aspirin. Among them, 5a and 5b which bear the best anti-inflammatory activity exhibited significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…In a recent publication, Jiang et al reported a series of new conjugates of aspirin having one “phenolic acid antioxidant” group ( p -coumaric acid, ferulic acid, or caffeic acid) connected through a diol linker to the carboxylic acid group present in aspirin. These prodrugs showed considerable anti-inflammatory activity (croton oil-induced mice-ear swelling) without significant GI side-effects; one of the diol linkers used by Jiang’s group was tyrosol, which is the protecting group we used in this work to form NSAID esters, meaning that it is probably not essential to have the second (additional) phenolic acid antioxidants linked to tyrosol to maintain the anti-inflammatory profile of the corresponding NSAID or to decrease its ulcerogenic effects.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication, Jiang et al reported a series of new conjugates of aspirin having one “phenolic acid antioxidant” group ( p -coumaric acid, ferulic acid, or caffeic acid) connected through a diol linker to the carboxylic acid group present in aspirin. These prodrugs showed considerable anti-inflammatory activity (croton oil-induced mice-ear swelling) without significant GI side-effects; one of the diol linkers used by Jiang’s group was tyrosol, which is the protecting group we used in this work to form NSAID esters, meaning that it is probably not essential to have the second (additional) phenolic acid antioxidants linked to tyrosol to maintain the anti-inflammatory profile of the corresponding NSAID or to decrease its ulcerogenic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Still scientists have performed many experiments to obtain new different derivatives of ASA mostly to avoid aspirin-induced gastrointestinal effects including decreasing the acidity and increasing the pharmacological activity of the new designed aspirin-like drugs ( Khalikov et al, 2006 ; Jiang et al, 2010 ; Huang et al, 2012 ; Hussain et al, 2013 ). Recently, the new hydrophobic analogs of aspirin were developed showing inhibition of the production of pro-inflammatory and enrichment of anti-inflammatory cytokines ( Kalathil et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…水杨酸作为重要有机原料中间体, 广泛用于医药、 农药及食品添加剂的研究. 含水杨酸片段的化合物往往 具有抑菌 [1] 、抗炎 [2] 、抗肿瘤 [3] 等多种生物活性. 近些年 来, 该类衍生物在抗癌方面的研究逐渐增多, 如: 2011 年, Yamaguchi 等 [4] 研究发现通过水杨酸衍生物制备的 前体药物 a 作为细胞凋亡诱导剂对肿瘤细胞有抑制作 用, 尤其是对恶性黑色素瘤细胞效果显著; 2013 年, 王 杰等 [5] 报道了水杨酰芳胺类化合物 b 对四种癌细胞 A-549, MCF-7, SGC-7901, Bel-7402 有不同程度的抑制 活性; 2007 年, Gasco 等 [6] 报道 c 类衍生物对结肠癌、膀 胱癌及前列腺癌有很好的治疗效果; Zhu 等 [7] 2010 年研 究发现 d 系列衍生物可选择性作用于 VEGFR-2 亚型, 活性最好的化合物 IC 50 到达 3.8 nmol/L; 2009 年, Pickens 小组 [8] 发现天然活性物 e 中的水杨酸部分是该类物质抗 癌的重要片段; 2011 年, Djurendić 等 [9] 自 1986 年, Giguere 研究小组报道微波在化学合成 的应用以来, 微波辅助合成可加速反应并提高产率的研 究不断增加, 在有机、药物合成领域的应用范围越来越 广 [16,17] .…”
unclassified